Punitive Policy of North-West Army and Its Implementation on the Approaches to Petrograd in Autumn of 1919 - I. S. Ratkovsky (Научный диалог, 2020)
The article analyzes the information about the punitive practice of the North-West Army in autumn of 1919 on the outskirts of Petrograd. Comments are made on the events that took place in the largest Petrograd suburbs - Gatchina, Pavlovsk, Detsky Selo and other closely located settlements after their transfer to the control of the White Army. It is noted that it was there that mass cases of capital punishment were recorded. The dynamics of the White repressions during the offensive on Petrograd is traced. It is reported that cases of release at the request of the local population were recorded. The novelty of the study is seen in attracting new sources to write the article. The article is based on the materials of a special commission to identify cases of white terror, recollections of residents of cities and military units, orders of the white command. Quantitative data on cases of white terror revealed at that time are analyzed. Special attention is paid to the facts of violence against the Jewish population. Statistics on the use of the death penalty are provided. The conclusion is made that the punitive practice of this period was carried out by the military courts, and to an even greater extent - through unprotected executions by the officers.